THE ETHNICAL CONFLICT IN THE EAST OF ANDALUSE DURING THE DOMENTIONS ERA 422-484AH 1030 – 1091 AD AMIR MUJAHID ALAMERI (A.C 436AH- 1045AD) PATACE AS EXAMPLE - Ramo, Omer Rahseer (Journal of Duhok University, 2018)
The era of king of Domention  the successors of Amawiyan successions with its inclusive of glory, prosper degemeration and disasters as all Besides the treasure of the ancient time was divided upon domenations and groups of Various sex religion and colors . The Andalusian United Country was splited and was ruld by Multipule chief's diversed politically socially and mentally whish was the man resons of the political dissociation that associated and approaehwd Andaluseian part altogether. Dne to this eash group detached from the other, dwelled in one of these group were 'The Sagaliba' these who dwelled in the East of Andalusa espeaially Daniya and the east Billiar Island ,After they reagained power and strenght on Arabi behalf they started attaching them in many Varioun ways. This  paper Shed light upon the ethnicl Conflict that started from The East of Andalues and precisely in one of its Amirs palace 'Mujahid ALAameri' where the Couflicte Started , ruled by chrestion man Called Ibn Garssiah.